THE INFLUENCE OF JOB SATISFACTION AND WORK EXPERIENCE ON LECTURER PERFORMANCE OF PAMULANG UNIVERSITY - Wahyudi, Wahyudi (Sekolah Menengah Kejuruan (SMK) Pustek, 2018)
The purpose of this research is to know the effect of job satisfaction and work experience on lecturer performance of Pamulang University. The research design used is quantitative with descriptive method. The analysis method used is multiple linear regression analysis with a sample of 150 and the sampling technique used is proporsionate random sampling. Furthermore, the research is done by testing the stages of analysis that includes descriptive analysis of questionnaires, validity test, reliability test, linear regression test, correlation coefficient test, partial test (t test), simultaneous test and determination test. Regression analysis results proved, Job satisfaction has a significant positive effect on the performance of 0.557, tcount 6.751 and a significance value of 0.000 smaller than 0.05. Work experience has a significant effect on performance of 0.451, the tcount of 5.467 and the significance value of 0.000 is smaller than 0.05. Simultaneous analysis proved job satisfaction and work experience have positive and significant effect on performance value of F arithmetic of 72.201, significance value of 0.000 and determination coefficient of 0.744.  It?s means, job satisfaction and work experience able to explain the performance of 74.4% while the rest of 25.6% is explained by other variables